Application of Apriori Algorithm to Determine Sales of Traditional Foods - Siti Nurajizah; Normah Normah; Nurfitriani Nurfitriani (Paradigma, 2023)
Competition in the food sales industry is growing, making business owners have to be creative to increase sales turnover. Sales activities that occur every day make sales data increase. Researchers intend to make data on Traditional Restaurant as the basis for data mining processing on food sales using the apriori algorithm. The application of the Apriori Algorithm aims to find the most item combinations based on transaction data and then form association patterns from combinations of items. Association patterns are formed with a minimum support value of 10% and a minimum confidence value of 40% which results in 3 association rules and the most sold food products are Krupuk Bangka and Karedok with a support value of 0.105% and a confidence value of 0.583%